Postoperative imaging of orthopaedic hardware in the hand and wrist: is there an added value for tomosynthesis?. Issue 2 (February 2018) - De Silvestro, A.; Martini, K.; Becker, A.S.; Kim-Nguyen, T.D.L.; Guggenberger, R.; Calcagni, M.; Frauenfelder, T.
Abstract : Aim: To prospectively investigate digital tomosynthesis (DTS) as an alternative to digital radiography (DR) for postoperative imaging of orthopaedic hardware after trauma or arthrodesis in the hand and wrist. Materials and methods: Thirty-six consecutive patients (12 female, median age 36 years, range 19–86 years) were included in this institutional review board approved clinical trial. Imaging was performed with DTS in dorso-palmar projection and DR was performed in dorso-palmar, lateral, and oblique views. Images were evaluated by two independent radiologists for qualitative and diagnosis-related imaging parameters using a four-point Likert scale (1=excellent, 4 not diagnostic) and nominal scale. Interobserver agreement between the two readers was assessed with Cohen's kappa (k). Differences between DTS and CR were tested with Wilcoxon's signed-rank test. A p -value <0.05 was considered statistically significant. Results: Regarding image quality, interobserver agreement was higher for DTS compared to DR, especially for fracture-related parameters (delineation osteosynthesis material [OSM]: KDTS  0.96 versus KDR  0.45; delineation fracture margins: KDTS  0.78 versus KDR  0.35). Delineation of fracture margins and delineation of adjacent joint spaces scored significant better for DTS compared to DR (delineation fracture margins: DTS 1.54, DR 2.28, p  0.001; delineation adjacent joint spaces: DTS 1.31, DR 2.24, p  0.001). Regarding diagnosis-related findings, interobserver agreement was almost equal. DTS showed a significant higher sharpness of fracture margins (DTS 1.94, DR 2.33, p  0.04). Mean dose area product (DAP) for DTS was significant higher compared to DR (mean DR 0.219 Gy·cm 2, mean DTS 0.903 Gy·cm 2, p  0.001). Conclusion: Fracture healing is more visible and interobserver agreement is higher for DTS compared to DR in the postoperative assessment of orthopaedic hardware in the hand and wrist. Highlights: Digital tomosynthesis provides higher interobserver agreement. Digital tomosynthesis provides better delineation of fracture margins. Better visibility of fracture healing is indicated by digital tomosynthesis.